The Jews in the Medieval Polish Economy: Some Thoughts on the Historiography of the Twentieth Century - Komornicka, Jolanta N. (History compass, 2009)
This essay was runner-up in the 2007 History Compass Graduate Essay Prize, Europe Section. The historiography of medieval Jewry has often by-passed the place of Jews in Poland, leaving that region for early modern scholars to tackle. Yet Poland had a significant Jewish population by the thirteenth century, though ascertaining its origins has been an issue of considerable debate among scholars and one heavily influenced by modern prejudices. As the scholarship has pulled itself from the anti-Semitic morass of the early twentieth century, gradually greater weight has been given to the place of Jews in Polish communities apart from the stereotyped role of moneychanger and royal financer. Yet East and West have still to come together to provide a better nuanced understanding of both the Jews in Europe and the growth of cities and communes along the eastern border of the Latin West.